The Gen Z Accountant: Bridging Digital Skills and Traditional Practices - Putri, Diana; Nor Rahma Rizka, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The accounting profession is experiencing a profound transformation as digital technologies, including artificial intelligence and data analytics. This change calls for a new generation of accountants, particularly Generation Z, who are recognized as digital natives. This paper uses the narrative literature review method to explores the educational strategies necessary to bridge the gap between digital skills and traditional accounting practices. By adopting active learning methodologies and prioritizing technology focused training, educators can enhance student engagement and foster a culture of innovation in accounting education. The study advocates for ongoing professional development to ensure that future accountants possess the technological acumen required to navigate the digital landscape effectively. The integration of digital skills training into accounting curricula is not only essential for individual employability but also for the sustainability and growth of the accounting profession in an increasingly digital world.